Pengaruh Pelayanan Prima dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen pada Toko Zae Prima Sibolga - Meiman Saputra Gulo; Rosmita Ambarita; Azriadi Tanjung (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study examines the effect of service excellence and product quality on consumer purchasing decisions at Toko Zae Prima Sibolga. A quantitative descriptive method was employed with a sample of 50 respondents using questionnaires and interviews. The results show that service excellence positively affects purchasing decisions (r = 0.269), while product quality has a stronger effect (r = 0.531). Multiple regression analysis indicates that both variables simultaneously explain 52.5% of the variation in purchasing decisions. The t-test and F-test confirm that both variables significantly influence purchasing decisions (p < 0.05). The findings highlight the importance of enhancing product quality supported by excellent service to encourage consumer purchase decisions.